Les mauvais jardinier: a reassessment of the myths and music of Kaikhosru Shapurji Sorabji - Abrahams, Simon John (London, 2001)
University of London, King's College. A dissertation submitted to the school of humanities in candidacy for the degree of doctor in philosophy in the department of music, 2001